Economic and Financial Viability of Coconut Sugar Agribusiness in Kokap District, Kulon Progo Regency - Ahmad Akbar Maulana; Fahri Okoye (Jurnal Agroteknologi dan Inovasi Pertanian, 2026)
Coconut sugar is one of the key agro-based products derived from coconut plants and widely developed in Kapanewon Kokap, Kulon Progo Regency, Indonesia. Understanding the business scale, profitability, and future prospects of this commodity is essential to support sustainable rural economic development. Therefore, this study aims to analyze the financial feasibility of coconut sugar enterprises in the study area.The research was conducted in Kapanewon Kokap and involved 100 coconut sugar artisans selected using a purposive sampling approach. Data were collected through field surveys and structured interviews. The financial feasibility analysis employed several key indicators, including the Revenue-Cost (R/C) ratio, capital productivity, and Break Even Point (BEP), covering production, revenue, and selling price dimensions.The results show that coconut sugar enterprises are financially feasible and profitable. The R/C ratio was calculated at 1.18, indicating that the business generates returns exceeding total production costs. Capital productivity reached 18%, reflecting efficient utilization of invested capital. Furthermore, the BEP analysis revealed that the break-even production level was 1.82 kg, the break-even revenue was IDR 39,822 per month, and the break-even selling price was IDR 3,813 per kg. These findings demonstrate that coconut sugar production operates above the minimum threshold required to avoid losses.In conclusion, the coconut sugar business in Kokap District, Kulon Progo Regency is financially viable and has promising potential for further development.